Educational exercises according to the kinematic variables in learning the approximate sprint stage of the Long jump jumpers - علي فؤاد فائق Omar Mizhar Malik (Mustansiriyah Journal of Sports Science, 2024)
The research aims to identify:Knowing the effect of educational units according to kinematic variables in learning the approximate run stage of the wide jumpers.The experimental approach was used, and (5) students were selected from the first stage / College of Basic Education, Department of Physical Education and Sports Sciences, Al-Mustansiriya University, for the academic season 2021-2022.The results revealed that there is a positive effect between the results of the pre and post tests of the two research groups and in favor of the post tests in learning the educational units according to the kinematic variables in learning the approximate run stage of the broad jumpers under study.It has been recommended to train teachers to use modern methods during the learning process as educational units according to the kinematic variables in learning.